Konsep Islam dalam Mengendalikan PerilakuAntisosial Remaja - Abidin, Zaenal (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2008)
family life in modern era indicated erosion of parent's role, responsibility, ond core to educate teenager through their maturity. Therefore, mo/adoptive (ontisociol) teenager od ond behavior that con harm other people. It is because their psychological condition is unstable ond influence of amoral culture, Â cruelty, violence, ond lock of attention ond control of family, school, ond society. If didn't give much core, its con deprive teenager future, so we need urgent alternative solution, namely: return to fundioning family, school ond society to enhance ond educate positive religious values of teenager, involved teenogeron off socio/ religious Â odivity ond toke advocated ond consultative odion on every trouble ond their life problems.